The Dynamics of Enterprises in Romania from the Perspective of their Performance during 2015-2022 - Puscaciu, Rose-Marie (The Journal of Accounting and Management, 2024)
Romanian economy has faced significant changes, reflected in the structure and dynamics of enterprises, during last years. This study analyzes the dynamics of enterprises in Romania, from the perspective of the number of employees and turnover, during 2015-2022. This research highlights the differences of the typology of enterprises, the dynamics of their numerical variation, as well as the results of the challenges and opportunities, associated with adaptation to the economic and technological changes, going to the dynamics of the number of employees and turnover, and using statistical data. The conclusions offer the perspective on future transformations and recommendations for the stimulation of innovation and the sustainable growth of the competitiveness of Romanian enterprises in the current global context. This analysis contributes to the understanding of economic dynamics and to the formulation of strategies for the consolidation and development of the private sector of Romania in the coming years.